A altura e a roçada do pasto no fim do inverno influenciam o perfilhamento a partir da primavera do capim-marandu previamente manejado sob pastejo diferido? - Carvalho, Bruno Humberto Rezende (2019)
The study of the dynamics of tillering on spring allows to know the mechanisms by which the forage plant resumes its regrowth, after the adverse weather conditions prevailing in winter. The objective of this work was to determine the effect of the height and mowed of the previously deferred pasture about the tillering of Brachiaria brizantha cv. Marandu syn. Urochloa brizantha cv. Marandu (capim-marandu) during the spring and the early the summer. Four pasture conditions at the end of winter was evaluited: short (15,1 cm e 4.600 kg/ha de DM), medium (23,2 cm e 5.940 kg/ha de DM), tall (31,4 cm e 7.640 kg/ha de DM) and tall/mowed (31,3 cm e 7.200 kg/ha de DM, however mowed to 8.0 cm). A completely was randomized design, and with three replications. In October, low and high/mowed pastures had tiller appearance rate (TApR) and stability index of the tiller population (SI) greater that medium and tall pastures. In the remaining months, TApR and SI were the same for all pasture conditions. SI was very high in October, declined in November and December and increased again in January. In October, the tiller mortality rate (TMoR) was lower in the low pastures, intermediate in the medium and high pastures, and greater in the high/mowed pastures. The percentage of young tillers was greater in the medium and tall pastures, in relation to the short and tall/mowed, a pattern of response contrary to that observed for the percentage of mature tillers. The percentage of old tillers was greater in the tall pastures, intermediate in the short and medium pastures, and lower in the tall/mowed pastures. Deferred and shorter marandu palisadegrass pastures at the end of winter showed greater stability of the tiller population and tillering in early spring compared to tall pastures. The mowing of marandu palisadegrass at the end of winter does not compromise the stability of the tiller population from spring.